Pengaruh Kreativitas dan Motivasi Kerja terhadap Produktivitas Guru Pendidikan Agama Islam Sekolah Dasar Sekecamatan Baturetno Kabupaten Wonogiri - Nurul Zuliawati (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
The purposes of this study are: (1) to determine the influence of creativity and productivity of Islamic Education (PAI) teachers of all primary schools in district Baturetno, Wonogiri of 2015/2016 (2) to determine the influence between work motivation and productivity of Islamic Education (PAI) teachers of all primary schools in district Baturetno, Wonogiri of 2015/2016 (3) to determine the influence of creativity and work motivation and productivity of Islamic Education (PAI) teachers of all primary schools in district Baturetno Wonogiri of 2015/2016. This research was conducted at all elementary schools of Baturetno, Wonogiri districts consisted of 32 schools. The method used in this study was a quantitative correlation. Methods of data collection used a questionnaire. The conclusions of this study are (1) There is an influence between creativity and productivity of Islamic Education (PAI) teachers of all primary schools in district Baturetno. (2) There is an influence between work motivation and productivity of Islamic Education (PAI) teachers of all primary schools in district Baturetno. (3) There is an influence between creativity and work motivation as well as productivity of Islamic Education (PAI) teachers of all primary schools in district Baturetno.Keywords: Influence of creativity, Work motivation, Teacher productivity